Laparoscopic management of residual gallbladder with calculi: a case report - Kundra, Dhruv; Hood, Mitesh Mohan (International Surgery Journal, 2025)
Residual gallbladder with calculi is a rare but significant complication following laparoscopic cholecystectomy. This condition can lead to persistent abdominal symptoms and poses diagnostic and therapeutic challenges. It often occurs when remnants of the gallbladder are unintentionally left behind during surgery, resulting in complications similar to those experienced prior to the procedure. We present the case of a 39-years-old female who experienced ongoing abdominal discomfort after undergoing laparoscopic cholecystectomy. A diagnostic laparoscopy revealed a residual gallbladder containing multiple calculi. The condition was successfully treated laparoscopically, alleviating her symptoms. This case underscores the need for a high index of suspicion for residual gallbladder complications in patients with recurrent biliary symptoms post-cholecystectomy. It highlights the importance of meticulous surgical techniques during initial procedures and reviews relevant literature on diagnostic modalities and treatment protocols, emphasizing effective management strategies for this uncommon but impactful condition.